ANALISIS YURIDIS TENTANG PENERAPAN NOODWEER EXCES TERHADAP PEMBELAAN DIRI DALAM TINDAK PIDANA PEMBUNUHAN DITINJAU DARI PERSPEKTIF HAM - Brigita Teselonika Tombokan; Dani Pinasang; Deizen Rompas (Universitas Sam Ratulangi, 2023)
Abstract The aims of this study are: 1) to examine and analyze the application of sanctions for the perpetrators of murder in cases of noodweer excesses; and 2) knowing how to apply noodweer excesses in Indonesian criminal justice decisions. This research was conducted using qualitative research methods with a normative-juridical approach as seen from legislation or a conceptual approach using secondary data which will then be analyzed qualitatively. Obtaining the materials needed in the preparation of this thesis, the authors have taken several methods of research, such as: 1) library data collection; and 2) research data processing both deductively and inductively. Based on the description in the discussion chapter, the authors draw several conclusions, as follows: 1) it can be judged that from one example of a case that has occurred in Indonesia, which the author discusses in the discussion, namely Decision Number: 26/PID.B/2014/PN.ATB the application of sanctions for the crime of murder has no value of justice in the imposition of the decision. Because this is not in accordance with Article 49 paragraph 2 of the Criminal Code which states that anyone who commits a forced defense that goes beyond the limits to protect himself, property or other people cannot be sentenced to a crime; 2) Indonesia is a constitutional state where everything in the form of private and public is regulated by law, Indonesia is also not a country that adheres to the understanding of absolute human rights. There are always limitations that can be reduced or taken from every citizen, for example the freedom of a person who has been sentenced to a criminal sentence. Therefore, forced defense that exceeds the limit (Noodweer Exces) which results in death for people who try to attack the dignity and fundamental rights of others, is not something that can be categorized as a violation of human rights as long as the specified limits and principles have been fulfilled. Keywords: murder; crime; justice; noodweer excesses Abstrak Tujuan dari pada penelitian ini, yaitu: 1) mengkaji dan menganalisa penerapan sanksi pelaku pembunuhan dalam kasus tindak pidana noodweer exces; dan 2) mengetahui bagaimana penerapan noodweer exces dalam putusan peradilan pidana Indonesia. Penelitian ini dilakukan dengan menggunakan metode penelitian kualitatif dengan pendekatan normatif yuridis yang dilihat dari perundang-undangan atau pendekatan konseptual dengan menggunakan data sekunder dan selanjutnya akan dianalisis secara kualitatif. Memperoleh bahan-bahan yang diperlukan dalam penyusunan skripsi ini, penulis telah menempuh beberapa cara penelitian, seperti: 1) pengumpulan data kepustakaan; dan 2) pengolahan data penelitian baik secara deduktif dan induktif. Berdasarkan uraian dalam bab pembahasan, maka penulis menarik beberapa kesimpulan, sebagai berikut: 1) dapat dinilai bahwa dari salah satu contoh kasus yang pernah terjadi di Indonesia, yang penulis bahas didalam pembahasan yakni Putusan Nomor: 26/PID.B/2014/PN.ATB penerapan sanksi tindak pidana pembunuhan tidak mempunyai nilai keadilan di dalam penjatuhan putusannya. Karena hal tersebut tidak sesuai dengan pasal 49 ayat 2 Kitab Undang-Undang Hukum Pidana yang menyatakan bahwa barang siapa melakukan pembelaan terpaksa yang melampaui batas untuk melindungi diri, harta benda, atau orang lain tidak dapat dijatuhi pidana; 2) Indonesia adalah negara hukum yang segala sesuatu yang berbentuk privat maupun publik diatur dengan hukum, Indonesia juga bukan negara yang menganut paham Hak Asasi Manusia yang bersifat Mutlak. Selalu ada batasan-batasan yang dapat dikurangi atau diambil dari setiap warga negara contohnya kemerdekaan dari seorang yang sudah dijatuhi putusan pidana. Maka dari itu pembelaan terpaksa yang melampaui batas (Noodweer Exces) yang mengakibatkan kematian bagi orang yang mencoba menyerang martabat dan hak fundamental orang lain, bukan sesuatu yang dapat dikategorikan sebagai pelanggaran hak asasi manusia asalkan batasan dan prinsip-prinsip ditentukan telah terpenuhi. Kata kunci: pembunuhan; pidana; peradilan; noodweer exces